Optimizing relativistic energy density functionals: Covariance analysis - Nikšić, T.; Paar, N.; Reinhard, Paul-Gerhard; Vretenar, D. (Journal of Physics G: Nuclear and Particle Physics, 2015)
The stability of model parameters for a class of relativistic energy density functionals, characterized by contact (point-coupling) effective inter-nucleon interactions and density-dependent coupling parameters, is analyzed using methods of statistical analysis. A set of pseudo-observables in infinite and semi-infinite nuclear matter (SINM) is used to define a quality measure χ2 for subsequent analysis. Uncertainties of model parameters and correlation coefficients between parameters are computed, and the eigenvectors and eigenvalues of the matrix of second derivatives of χ2 at the minimum are evaluated. Using these quantities, the stability of the density functional in nuclear matter is examined, and weakly and strongly constrained combinations of parameters are determined. In addition, uncertainties of observables that are not included in the calculation of χ2 are analyzed: binding energy of asymmetric nuclear matter, surface thickness of SINM, binding energies and charge radii of finite nuclei.
CRIS-Team Scopus Importer:2023-07-24
Keywords: correlation analysis; error estimates; nuclear energy density functionals; uncertainty quantification